Key Policies and Legislation Underpinning Post-School Transition Practices for People with Disabilities in the Republic of Ireland - Connolly, Leanne (International Journal of Educational and Life Transitions, 2023)
Internationally, key policies and legislation have begun to be influenced by a move towards a rights-based approach to education and employment for people with disabilities. The ratification of the United Nations Convention on the Rights of Persons with Disabilities (CRPD) (2006), in the Republic of Ireland in 2018, initiated a number of action plans and strategies to uphold the rights of people with disabilities and support the transition into further and higher education and progression to employment. While there have been modest increases in education and employment participation rates of some people with disabilities, the Republic of Ireland continues to underperform in supporting transition to further and higher education and progression into the workplace, particularly for those with intellectual disabilities. The absence of transition legislation and policies, combined with the Republic of Ireland’s multitrack and largely segregated system of education at primary and secondary levels, have resulted in persistent system-level barriers in accessing their rights as set out in the CRPD (2006). The purpose of this position paper is to critique current legislation and policies that influence educational provision for all people with disabilities, including where specified people with intellectual disabilities, as they transition from school to further and higher education in the Republic of Ireland. It highlights the continuing challenges of operating within a largely segregated system, with little advancement towards the Republic of Ireland’s commitment under Article 24 (5) and 27 (d) of the CRPD (2006).